Design and Development of an Automatic Angklung Robot Based on Microcontroller - Wicaksono, Agung Rizaldi; Subur, Joko; Taufiqurrohman, Muhammad (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2023)
The angklung is a traditional musical instrument from West Java, Indonesia. It can be played both individually and in groups. Playing the angklung requires precision in terms of tempo, rhythm, pitch, and beats to ensure that the music aligns with the intended song and is enjoyable to listen to. Therefore, not everyone can play the angklung, as it demands skill to achieve the right tempo, pitch, rhythm, and beats. To address this issue, a solution was developed, which involved creating a system and device capable of playing the angklung automatically. In this research, a system was designed to move the angklung automatically, simulating a robot, and it is referred to as the "angklung robot." This angklung robot consists of a set of 16 notes, and the electrical components used include an Arduino Mega 2560 as the microcontroller, a 16-channel relay module, motor drivers, a micro SD module. To play a song, the device uses a score file that has been converted and stored on a micro SD card, adjusting the tempo to match the desired Beats Per Minute (BPM).Through several experiments, the angklung robot successfully played 10 pre-composed songs with a 100% accuracy rate. According to the opinions of 10 music enthusiasts who were surveyed, the level of accuracy in which the angklung robot played the songs was 90%.This innovation brings automation to the traditional art of playing the angklung, making it accessible to a wider audience and ensuring consistent and precise musical performances.